Does Mother Nature Corrupt Natural Resources, Corruption, and Economic Growth - Leite, Carlos (International Monetary Fund, 1999)
This paper argues that natural resource abundance creates opportunities for rent-seeking behavior and is an important factor in determining a country's level of corruption. In a simple growth model, we illustrate the interrelationships between natural resources, corruption, and economic growth, and discuss potential anti-corruption policies. We show that the extent of corruption depends on natural resource abundance, government policies, and the concentration of bureaucratic power. Furthermore, the growth effects of natural resource discoveries and anticorruption policies crucially depend on the economy's state of development. We empirically corroborate the model's implications in a cross-country framework with both corruption and growth endogenized